Microvascular abnormalities between anti-TIF1-γ-associated dermatomyositis with and without malignancy - Sehreen Mumtaz; Jordan Phillipps; Megan M. Sullivan; Maximiliano Diaz-Menindez; Benjamin Wang; Vikas Majithia; Emily Craver; Florentina Berianu (BMC Rheumatology)
Abstract Background Dermatomyositis (DM) is an immune-mediated myopathy characterized by proximal muscle weakness, inflammation, and cutaneous manifestations. Up to 25% of DM patients have an associated malignancy. Those with cancer-associated DM often face worse prognoses, poorer treatment responses, and reduced survival rates. Interestingly, anti TIF1γ-positive DM patients are notably at increased risk for malignancy, yet the underlying mechanisms and clinical correlation remain poorly understood. Nailfold video capillaroscopy (NVC) is a safe, non-invasive method for assessing vascular abnormalities, previously explored in various DM subsets but not specifically in anti TIF1γ-positive DM patients with malignancy. This study aims to characterize NVC findings in anti-TIF1γ-positive DM and assess their clinical relevance, particularly in malignancy-associated cases. Methods A retrospective review at Mayo Clinic, Jacksonville from January 1st, 2010 to May 16th, 2024 was conducted. 19 cases with anti TIF1γ-positive DM and 18 idiopathic inflammatory myopathy controls were included. Results We observed anti TIF1γ-positive DM cases to have significantly increased capillary density loss and higher microhemorrhages (p = 0.057). Cases also had higher frequencies of dilated capillaries, capillary ramifications, and capillary disorganization. Although no statistically significant differences in NVC pattern were identified in cancer vs. non-cancer anti TIF1γ-positive DM, there were greater hemorrhages and ramifications noted in the cancer anti TIF1γ-positive subset. Conclusion This study investigated NVC differences among anti TIF1γ-positive DM with malignancies versus idiopathic inflammatory myopathy controls. Our findings indicate promising microvascular differences with a potential for predicting cancer development that warrant further exploration in larger studies. Clinical trial number Not applicable.